L’urgence comme chronopolitique - Edouard Gardella (Temporalités)
The public problem of housing exclusion has been regulated in France since the nineteen-eighties through a specific form of policy, known as social emergency. Before 2007, homeless people using emergency shelters suffered from the exclusive provision of short-period stays and consequently had a hard time planning their lives. The interaction between institutional and individual temporalities can be conceptualized as chronopolitics. Because of its exhausting effects on the homeless, chronopolitics was denounced by activists who demanded that continuous stays in shelters, adapted to specific needs, be considered a right. That new temporal ecology was promoted by a law passed in 2007. However, as a legal right it has remained ineffective to this day. Explanations are to be found at several levels of public policy: due to the scarcity of provision, emergency shelter managers resort to restricting the length of stays; structural scarcity is artificially maintained by restrictive State policy, which seeks to limit the demands made by the large number of people in difficulty; social workers feel uncomfortable about people considering the continuous use of shelters an unconditional right. The opportunity to benefit from continuous, non-commodified housing suffers from a lack of legitimacy.